From The Editor - Bakar, Osma (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
On behalf of the Center for Civilizational Dialogue, I would like to make this important announcement: the Centre has ceased to publish its bilingual journal known as Katha, Journal of the Centre for Civilizational Dialogue. The last pubclished issue of the Journal was Katha 3, 2007.